2012
DOI: 10.1182/blood-2011-08-375873
|View full text |Cite
|
Sign up to set email alerts
|

Role of SHP2 phosphatase in KIT-induced transformation: identification of SHP2 as a druggable target in diseases involving oncogenic KIT

Abstract: Intracellular mechanism(s) that contribute to promiscuous signaling via oncogenic KIT in systemic mastocytosis and acute myelogenous leukemia are poorly understood. We show that SHP2 phosphatase is essential for oncogenic KITinduced growth and survival in vitro and myeloproliferative disease (MPD) in vivo.Genetic disruption of SHP2 or treatment of oncogene-bearing cells with a novel SHP2 inhibitor alone or in combination with the PI3K inhibitor corrects MPD by disrupting a protein complex involving p85␣, SHP2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 39 publications
6
51
0
Order By: Relevance
“…Given the leukemogenic effect of activating PTPN11/Shp2 mutations or Shp2 overexpression in different types of human leukemia (30,33,34), Shp2 has emerged as an attractive therapeutic target for mechanism-based treatment of leukemia (30,35). It was demonstrated recently that a Shp2-inhibitory compound corrected oncogenic Kit-triggered MPN in mouse models (36). However, the multifaceted roles of Shp2 and Pten in hematopoietic cells revealed in this study raise caution for clinical use of specific Shp2 inhibitors for patients with Pten mutation or deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Given the leukemogenic effect of activating PTPN11/Shp2 mutations or Shp2 overexpression in different types of human leukemia (30,33,34), Shp2 has emerged as an attractive therapeutic target for mechanism-based treatment of leukemia (30,35). It was demonstrated recently that a Shp2-inhibitory compound corrected oncogenic Kit-triggered MPN in mouse models (36). However, the multifaceted roles of Shp2 and Pten in hematopoietic cells revealed in this study raise caution for clinical use of specific Shp2 inhibitors for patients with Pten mutation or deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the highly conserved active site shared by all mammalian phosphatases, identification of specific SHP2 phosphatase inhibitors has been difficult; however, within recent years, pharmacologic inhibitors of SHP2 phosphatase function have been identified [29,[46][47][48], and have demonstrated activity in mutant KIT-, gain-of-function PTPN11-, and FLT3-ITD-induced myeloproliferative neoplasms [27][28][29], all of which bear hyperactivation of SHP2. Based on these promising advancements, we anticipate that inhibition of SHP2 phosphatase activity using small pharmacologic molecules may yield a valuable adjuvant approach to therapies for acute myeloid leukemias and myeloproliferative neoplasms bearing SHP2 hyperactivation.…”
Section: Shp2 Phosphatase In Human Hematopoiesismentioning
confidence: 99%
“…However, while several knockout and knockdown studies have demonstrated that Shp2 is particularly important in hematopoietic development and hematopoietic stem cell function [20][21][22][23][24][25][26], none of these has directly examined the role of SHP2 phosphatase function in hematopoiesis. This is particularly of relevance, as pharmacologic inhibitors of SHP2 phosphatase activity are currently in development and have demonstrated activity in oncogene-induced myeloproliferative neoplasms [27][28][29]. Thus, the following studies utilized various SHP2 mutants either lacking the SHP2 phosphatase domain or bearing a loss-of-function point mutation or a gain-of-function point mutation reducing or increasing SHP2 phosphatase function, respectively, to define specifically the role of SHP2 phosphatase function in hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…SHP2 is required for the maintenance of HSCs and progenitor cells (8). Gain-of-function mutations in SHP2 cause a myeloproliferative disorder, and SHP2 is essential for oncogenic c-KIT transformation to myeloproliferative disease (9,10). Recently, the intracytoplasmic phosphatase of regenerating liver PRL2 was found to be important for SCFmediated HSC self renewal (11).…”
Section: Introductionmentioning
confidence: 99%